Optimization of analytical parameters for determination of iron, nickel and cobalt in plants with RP-HPLC - Çiftçi, Harun; Ölçücu, Ali; Ozkayat, Ahmet; Çiftçi, Tacettin (Chemical Publishing Co., 2009)
This study optimized the analytical parameters such as combination of mobile phase, pH of mobile phase, attempt effect of strange ions and current rate for simultaneous determination of iron, nickel and cobalt. 4-(2-Pyridiylazo)resorcinol (PAR) ligand is used for metal chelates. The metal-PAR chelates were separated on a Luna C18 siloxane bonded phase and eluted within 7.4 min of Co-PAR, 9.6 min of Fe-PAR and 12.4 min of Ni-PAR with methanol-water-acetonitrile-(l × 10'2 mol L"1) sodium acetate (55:40:2.5:2.5 v/v) (pH 5.3). Detection limits of process for Fe- PAR, Ni-PAR and Co-PAR under optimized conditions (500 nm) were found as 4.45,3.26 and 1.86 ?g L-1 respectively. The analysis of Fe, Ni and Co ions in plant samples under optimized conditions were carried out by HPLC.
Keywords: 4-(2-Pyridylazo) resorcinol; Cobalt; HPLC; Iron; Nickel; Trace element; UV-Visible